2016
DOI: 10.3126/ajms.v7i4.14614
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of drug prescription for the treatment of falciparum malaria in a medical college in Eastern India

Abstract: Background: Drug prescription pattern for the treatment of falciparum malaria differs widely from place to place; but there is also some intra organizational variation of prescription pattern of anti-malarial drugs for the treatment of falciparum malaria.Aims and Objectives: The present study was planned to study the drug utilization pattern for the treatment of falciparum malaria in a tertiary care teaching hospital in eastern India.Materials and Methods: It was a hospital based study conducted in the departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…18 15,20 Two other studies from India reported use of primaquine which varied from 12.5% to 56.7%. 16,18 In the present study the average number of drugs per prescription was 3.79 in children and 3.59 in adults. According to World Health Organization guideline of rational use of medicine, the average number of drug per prescription should be 1.6-1.8.…”
Section: Resultsmentioning
confidence: 40%
See 4 more Smart Citations
“…18 15,20 Two other studies from India reported use of primaquine which varied from 12.5% to 56.7%. 16,18 In the present study the average number of drugs per prescription was 3.79 in children and 3.59 in adults. According to World Health Organization guideline of rational use of medicine, the average number of drug per prescription should be 1.6-1.8.…”
Section: Resultsmentioning
confidence: 40%
“…In one study from a tertiary care hospital in Eastern India showed that artesunate (48.1%) and mefloquine (25.9%) were the most common antimalarials for falciparum malaria. 16 In another study from Karnataka reported quinine and artesunate mono-therapy in respectively 80% and 5% of falciparum malaria cases. 18 15,20 Two other studies from India reported use of primaquine which varied from 12.5% to 56.7%.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations